Cognitive characteristics and ischemic prognosis of quantitative white matter hyperintensities in adult moyamoya disease - Ziqi Liu; Xiaokuan Hao; Qi Duan; Chaoran Shen; Haojin Lyu; Junze Zhang; Jing Gu; Shihao He; Yanru Wang; Xilong Wang; Zhenyu Zhou; Ning Ma; et al. (Communications Medicine)
Abstract Background White matter hyperintensities (WMHs) are associated with long-term stroke and cognitive decline in the elderly population but differ from the young and middle-aged populations, especially for those with moyamoya disease (MMD). The aim of this study was to modify the Fazekas grade and quantitatively analyze the effects of WMHs on multiple cognitive domains and 2-year clinical ischemic events in adult MMD patients. Methods Adult MMD patients and healthy controls were recruited for a comprehensive cognitive assessment. Among 151 adult MMD patients, the average age was 41.78 ± 10.59 years and the male-to-female ratio was 0.94. Adjusted quantitative whole-brain, periventricular (PVWMHs), and deep WMHs (DWMHs) were included in the proportional hazards model to explore their relationships with 2-year ischemic events. Linear regression analysis was used to evaluate the correlation between the WMH burden in different brain regions and various cognitive domains. Results MMD patients present decreases in intelligence (P = 0.000), spatial working memory (P = 0.011), verbal working memory 1 (P = 0.000) and 2 (P = 0.000), mental rotation (P = 0.008), and executive inhibition (P = 0.011). Quantitative whole-brain log10WMHs (adjusted HR = 6.757, P = 0.001) and log10PVWMHs (adjusted HR = 8.824, P = 0.000) are independently associated with future ischemic events. The area under curve (AUC) of the quantitative PVWMH for the prediction of 2-year ischemic events is 0.701, which is better than that of the Fazekas grade (AUC = 0.561) (P = 0.000). Conclusions PVWMHs have greater potential effects on verbal working memory, attention, and simple subtraction in adult MMD patients when compared with DWMHs. An increase in PVWMHs could be an indicator of future ischemic events in adults with MMD. Clinical registration Clinical registration no. ChiCTR2200058251 URL: https://www.chictr.org.cn/ .